PENGARUH MEREK, KOMUNIKASI PEMASARAN DAN HARGA TERHADAP LOYALITAS DENGAN MINAT BELI ULANG SEBAGAI VARIABEL INTERVENING PADA PELANGGAN BRANCHLESS BANKING BTN KC KELAPA GADING SQUARE JAKARTA UTARA - Junaedi, Edy; Supriyadi, Supriyadi (STAI Asy-Syukriyyah, 2024)
The banking industry experiences difficulties in providing services to people who are far from banks, because it requires high cost. Bank BTN encourages the development of bank services without offices with Telkom through branchless banking or the agent laku pandai. To analize agent performance, research was carried out from the aspects of brand, marketing communication and price on customer loyalty through customer repurchase interest in transacting at laku pandai agents. Samples were taken as many as 105 respondents of customers. The data obtained were then processed using Smart PLS version 3 and analyzed using multiple linear regression analysis. This analysis includes reliability test, validity test, hypothesis testing through Ttest and Ftest as well as coefficient of determination (R2). Test results show based on bootstrapping, the P value 0.005 of brand partially have a positive and significant effect on repurchase intention and the P value 0.086 for brand partially does not have significant effect on loyalty. The P value 0.96 for marketing communication partially does not have significant effect on loyalty and likewise the p value 0.52 for marketing communication on repurchase intention. The P value for price on loyalty is 0.97, so the price has no significant effect, but the p value for price on repurchase intention is 0.00, so price on repurchase intention has a significant effect and the p value for repurchase intention on loyalty is 0.00, meaning it has a significant effect.